PREFERENSI KONSUMEN DAN STRATEGI PEMASARAN PRODUK OLAHAN KELAPA KOPYOR - Valentina Sokoastri (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2020)
Many people like Kopyor coconut. Kopyor Coconut formed from an abnormal coconut fruit that is only be found in a rare number of the normal coconut tree. Unfortunately, the demand for kopyor coconut is not followed by the supply, in other words, the supply of Kopyor Coconut is still under the demand. Following this opportunity, Indonesian Biotechnology Plantation Research Center, PT Riset Perkebunan Nusantara invented a plant tissue isolation method that can produce 90 to 100 per cent of kopyor coconut fruit. Thus, it is necessary to study consumer preferences and marketing strategy to distribute Kopyor product in the right plan. This study uses a quantitative approach by capturing 50 respondents in incidental sampling. The data is then processed descriptively using Microsoft excel to see consumer preferences and its 4P (Product, Place, Promotion, Price). From the data analysis obtained as follows: 1. Consumer preferences of kopyor coconut (Kosudu) are quite well and acceptable by the costumers. 2. The product, place and promotion need to be regenerated, but for the price is quite stable. 3. Need marketing strategies to improve product quality, such as (brand, packaging, and quality control), place such as (online delivery system and retail approach, last but not least the promotions such as (discounts and advertising).